Analisis Sosialisasi Politik Relawan Demokrasi Basis Warga Internet Kota Medan Pemilihan Umum Tahun 2019 - Mas Indra Putra Alamsyah; M.Arif Nasution; R. Hamdani Harahap (Perspektif: Jurnal Ilmu-ilmu Sosial)
Netizen Basis Democracy Volunteers are one of the community groups that carry out election socialization activities and educate democratic values to their segments of society or Netizens in the 2019 Elections. This study discusses the election socialization activities carried out by Netizen Basis Democracy Volunteers. The purpose of this research is to analyze the patterns of election socialization using the variable of political socialization. The author uses qualitative methods, data collection through interviews, documentation and literacy studies. The results showed that Netizen-Based Democracy Volunteers carry out election socialization activities using media and non-media facilities through volunteer and personal account posts. There are four patterns of socialization of Netizen-Based Democracy Volunteers, namely: Opening information posts, hanging out with Netizens, posting on social media and giveaway. For some people, especially Millennials, consider the Election socialization activity as an effort to represent the struggle to uphold people's sovereignty, this is supported by the composition of Netizen-Based Democracy Volunteers who are all students who are considered far from political interests, this is because Millennial is more familiar with social media so that it is easy and quickly keep abreast of information and relatively many have references. While some who refuse to assume that the socialization activities carried out by volunteers are less work activities and some even make fun of volunteers.